E-Court Paradigm Shift: Problems of Legitimacy Mechanisms of Electronic Evidence in State Administrative Procedure Law - Setiawan, Hafizh Daffa; Erhuma, Mohammed; Holish, Amarru Muftie (Indonesian State Law Review (ISLRev), 2023)
This study on the legitimacy mechanisms of electronic evidence within the State Administrative Procedure Law is intrinsically connected to Indonesia’s ongoing efforts to modernize its legal landscape. The acknowledgment of electronic information and documents as valid evidence aligns with Indonesia’s commitment to adapting its legal framework to the digital era. The legal issues explored within the context of the E-Court paradigm shift resonate with Indonesia's broader initiatives to enhance judicial efficiency and access to justice. As Indonesia grapples with the challenges of incorporating electronic evidence within its administrative procedures, the study sheds light on the specific hurdles faced within the Indonesian legal system. Regulatory complexities and resource constraints resonate with Indonesia’s broader struggle to harmonize its legal infrastructure with the demands of the digital age. Moreover, the study emphasizes the importance of a proportionate mechanism in addressing legitimacy concerns, aligning with Indonesia’s commitment to fostering a fair and balanced legal environment. The conclusion highlighting the critical role of the validation process reflects Indonesia’s dedication to ensuring the integrity and reliability of electronic evidence within the legal proceedings.